Depigmentation of Gingival Smoker's Melanosis Using Scalpel Surgical Technique: A Case Report - Syaify, Ahmad; ., Sutriyanti (KnE Medicine, 2022)
Background: Gingival pigmentation not only has an impact on aesthetics but also causes negative psychological effects. Gingival pigmentation is the coloring of the gingiva due to a variety of lesions and disorders caused by various endogenous and exogenous causes. Smoker’s melanosis refers to the pigmentation of the oral mucosa that occurs as a result of tobacco consumption. Gingival depigmentation is a periodontal plastic surgery process that uses a variety of procedures to eliminate hyperpigmentation, including scalpel, cryosurgery, electrosurgery, laser and others. Objective: To describe surgical procedures that maintain both cosmetic and functional requirements. Case Report: A 21-year-old man presented with complaints of inflammatory gingival enlargement and Smoker’s pigmentation of the maxillary and mandibular gingival melanosis. Surgical therapy was used to improve the appearance of the patient and avoid plaque retention. Conclusion: The scalpel approach is one of the most cost-effective methods, requiring only a basic armamentarium. It is highly recommended considering the limitations of equipment and that scalpel wounds heal more quickly than those treated with other techniques. Keywords: smoker’s melanosis, depigmentation, surgical scalpel technique, periodontal plastic surgery